Smart Gas Sensing by (Al/C/Si)-Doped Boron Nitride Nanomaterial Towards Grabbing Nitric Oxide: A Novel Applied Technique for Air Pollution Reduction by DFT Analysis - Mollaamin, Fatemeh (Scifiniti Publishing, 2025)
The electronic, magnetic, and thermodynamic properties of adsorption of toxic gases, including Nitric oxide (NO) by using Y (Y = Al, C, Si)-doped boron nitride nanocage (BN) have been investigated using density functional theory (DFT). The results denote that NO→Y–BN are stable compounds, with the most stable adsorption site being the center of the cage ring. Furthermore, the reported results of nuclear magnetic resonance (NMR) spectroscopy have exhibited the strength of covalent bonds between aluminum, carbon, silicon, and NO molecules toward toxic gas removal from the air. Based on the results of ∆ G a d s o amounts in this research, the maximum efficiency of Al, C, and Si atoms doping of BN for gas molecules adsorption depends on the covalent bond between NO molecules and Y–BN as a potent sensor for air pollution removal. Finally, the high selectivity of atom-doped boron nitride nanocage (gas sensor) for gas molecule adsorption has resulted in: Al ˃ C ˃ Si.